Effects of an 8-week strength training intervention on tibiofemoral joint loading during landing: a cohort study. - Czasche,MB; Goodwin,JE; Bull,AMJ; Cleather,DJ (BMJ Open Sport and Exercise Medicine, 2018)
Objectives: To use a musculoskeletal model of the lower limb to evaluate the effect of a strength training intervention on the muscle and joint contact forces experienced by untrained women during landing. Methods: Sixteen untrained women between 18 and 28 years participated in this cohort study, split equally between intervention and control groups. The intervention group trained for 8 weeks targeting improvements in posterior leg strength. The mechanics of bilateral and unilateral drop landings from a 30 cm platform were recorded preintervention and postintervention, as was the isometric strength of the lower limb during a hip extension test. The internal muscle and joint contact forces were calculated using FreeBody, a musculoskeletal model. Results: The strength of the intervention group increased by an average of 35% (P<0.05; pre: 133±36 n, post: 180±39 n), whereas the control group showed no change (pre: 152±36 n, post: 157±46 n). There were only small changes from pre-test to post-test in the kinematics and ground reaction forces during landing that were not statistically significant. Both groups exhibited a post-test increase in gluteal muscle force during landing and a lateral to medial shift in tibiofemoral joint loading in both landings. However, the magnitude of the increase in gluteal force and lateral to medial shift was significantly greater in the intervention group. Conclusion: Strength training can promote a lateral to medial shift in tibiofemoral force (mediated by an increase in gluteal force) that is consistent with a reduction in valgus loading. This in turn could help prevent injuries that are due to abnormal knee loading such as anterior cruciate ligament ruptures, patellar dislocation and patellofemoral pain.